Normalizacja i harmonizacja wymogów dotyczących wprowadzenia wyrobu do obrotu na terenie Unii Europejskiej jako działania warunkujące rozwój gospodarczy - Sługocka-Kołpaczyńska, Martyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
In the countries of the European Union a manufacturer, an importer, and an authorized representative have to meet the requirements for the type of goods. An action which allows to provide the same level of quality for all products is harmonization. As a rule harmonization is achieved by implementation of EU directives, which should by placed in the legal system of the Member States. But focus only on product quality may lead to generating large costs restraining economic developto achieve saving, users interests and protection of life and health.ment. Normalization should prevent this phenomenon. Normalization is a deliberate action adjusted to achieve saving, users interests and protection of life and health.Uniform rules concerning the placing on the market in every Member States directly provides the growth potential of the market and invites manufacturers and importers to act on the European market. By engaging in one-off activities they will gain access to a great and differentiated market. Additionally, the same requirements for the products promote technology development. Thus the interests of consumers are protected.
Keywords: normalizacja; harmonizacja; rynek europejski